Security validation of smartcard: MCOS - Yahya, Saadiah; Nik Omar, Nik Azmi (2010)
The National Fuel subsidy system planning in Malaysia should it persist would have elevated the Multi-purpose of MyKad. Malaysian government is planning for a new MyID system that can retrieve governmental related documents when dealing with 760 governments and agencies nationwide (The Star, 2010). This move will leverage the existing infrastructure of MyKad. The wider usage of MyKad may raise public concern regarding its security. Thus, there is a need for assessing the security of MyKad by an independent third party.This paper will first discuss vulnerability of smartcard by using the attack potential model (CCDB, 2008), and then the appropriateness of the current methods and tools to test the security of smartcard will be investigated.The study concludes that there is no yet a standard of security testing tool imposed on smartcard in Malaysia.The study promotes the developing of security testing tool for MyKad.